KETIDAKADILAN GENDER TOKOH UTAMA DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU - Rerin Maulinda; Fentiani Fentiani (fakultas sastra, 2022)
Fentiani. 171010700143. Gender Injustice The Main Character in the Novel Nayla by Djenar Maesa Ayu. Indonesian Literature. Faculty of Literature. Pamulang University. 202v2 The meaning of the word gender is often misunderstood only as gender differences, resulting in gender inequality which is manifested in the form of marginalization, subordination, stereotypes, violence, and workload. This study aims todescribe: (1) the forms of gender injustice in Djenar Maesa Ayu Nayla novel. The type of research conducted is descriptive qualitative research. The results obtained in this study are (1) gender injustice that occurs in the characters in the novel including marginalization, subordination, stereotypes, violence, and workload.Kata Kunci/Keywords: Injustice, gender, women.